So close - Corey Yuen.; Jeff Lau.; Eastern Film.; Columbi Pictures; Magna Vision (United States Columnbia Pictures; distributed in the Philippines by MagnaVision, 2002)
A crooked businessman brings in a pair og high-tech assassin sisters to murder his elder brother so he can take over the family's business empire. When a determined policewoman starts to put the pieces of the puzzle together, the businessman realizes that he must destroy all evidence...including the assassins and the cop!. The three women are left to fight for their lives, while helping each other along the way. With some of the best action scenes to appear on film this year.
Editor, Cheung Ka Fai ; music ; Sam Kao Kenjo Tan ; art director, Eddy Wong
Qi Shu, Vicki Zhao, Karen Mok, Seung-heon Song, Yasuaki Kurata.
VCD
Keywords: Science fiction films